1975
DOI: 10.1182/blood.v46.4.599.bloodjournal464599
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory observations on serum folate-binding protein

Abstract: We studied the effect of serum folate-binding protein (FBP) on folate radioassays and the relationship of the serum level of unsaturated FBP to the serum folate level in various clinical states. Our modification of a heat-extracted radioassay was compared to a whole serum radioassay. Our results confirmed the existence of elevated serum levels of unsaturated FBP in some normal subjects, in some women taking oral contraceptives, and in most patients with uremia. Elevated levels of unsaturated FBP will produce f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2002
2002
2002
2002

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
1
0
3
Order By: Relevance
“…25 This protein, now known as folate receptor, is increased in disease states like uremia and may produce intracellular folate deficiency in uremic patients, resulting in megaloblastic bone marrow changes. 26,27 The use of heparinized plasma in assays of FABP resulted in a decreased FABP concentration, which was partially regained after neutralization of heparin by protamine, 28 possibly indicating a shift in folic acid toward the intracellular compartment concentrations large enough to affect tHcy plasma concentration. The prolonged effect of low-molecularweight heparin (LMWH) seen in a subgroup of patients in this trial can be explained by the sustained effect of folic acid observed in several intervention studies 29 showing reduced tHcy up to 12 weeks after the cessation of folic acid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…25 This protein, now known as folate receptor, is increased in disease states like uremia and may produce intracellular folate deficiency in uremic patients, resulting in megaloblastic bone marrow changes. 26,27 The use of heparinized plasma in assays of FABP resulted in a decreased FABP concentration, which was partially regained after neutralization of heparin by protamine, 28 possibly indicating a shift in folic acid toward the intracellular compartment concentrations large enough to affect tHcy plasma concentration. The prolonged effect of low-molecularweight heparin (LMWH) seen in a subgroup of patients in this trial can be explained by the sustained effect of folic acid observed in several intervention studies 29 showing reduced tHcy up to 12 weeks after the cessation of folic acid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Eichner καυ συν. [127] εύρηκαν αυξημένη άκο'ρεστη δεσμευτυκη ΐκανο'τά του οροϋ προ'ς το φυλ λυκο'. Ή άκο'ρεστη δεσμευτυκη' υκανο'της τοϋ φορέως του όρου γυά το' φυλλυκο' έλέγχεταυ με' προσθήκη στο'ν όρο' 3 HPGA καυ κατο'πυν με'τρηση της ραδυενεργευ'ας ,πού 5ε'ν προσροφαταυ στο'ν εν εργό' άνθρακα.…”
Section: S'« It It λ λ It It It It It It It It It It It It It It It It It It It It It It It It It It It It It It It It It It It It It It unclassified
“…Εφόσον το φυλλικό οξύ απομακρύνεται κατά την αιμοκάθαρση, είναι δυνατό να εμφανισθούν μεγαλοβλαστικές αλλοιώσεις στο μυελό των οστών. Ιδιαίτερα επιρρεπείς είναι όσοι ασθενείς υποβάλλονται σε περιορισμό των πρωτεϊνών που προσλαμβάνουν (<60g την ημέρα) (Eichner 1975, Hemmeloff 1977, δε σιτίζονται επαρκώς λόγω ανορεξίας ή λαμβάνουν φάρμακα που παρεμβαίνουν στην απορρόφηση ή το μεταβολισμό του φυλλικού οξέος (λ.χ. διφαιλυλυδαντοΐνη, βαρβιτουρικά, χολεστυραμίνη, αντισυλληπτικά, μεθοτρεξάτη κ.λ.π.)…”
Section: ένδεια φυλλικού οξέοςunclassified
“…Τα επίπεδά του στον ορό είναι φυσιολογικά ή μειωμένα (Paine et al 1976). Οι χαμηλές τιμές στο αίμα δεν αποτελούν πάντοτε ένδειξη ιστικής έλλειψης της βιταμίνης, αλλά αποδίδονται στα αυξημένα σε ΧΝΑ επίπεδα του λευκώματος που συνδέει το φυλλικό οξύ (Eichner et al 1975).…”
Section: φυλλικό οξύunclassified